The effectiveness of personalized medication based on drug-related genes, for schizophre- nia patients with resistance to traditional drugs.: La eficacia de la medicación personalizada basada en genes relacionados con fármacos, para pacientes con esquizofrenia resistente a los fármacos tradicionales. - Zhou, Shujun; Zhang, Guangqin; Wang, Zhe; Wei, Long; Zhu, Min; He, Jinquan (Investigación Clínica, 2024)
We aimed to study the impact of personalized medication based on drug-related genes for schizophrenia patients with resistance to traditional drugs. One hundred and ten schizophrenia patients who sought treatment at our medical facility between June 2021 and February 2023 were chosen and divided at random into two groups: one group (n=55) received conventional medication, while the other group (n=55) received personalized medication based on their genetic profile. The study compared the levels of inflammatory cytokines and neurotrophic factors, as well as the scores on the Positive and Negative Symptoms Scale (PANSS), Brief Psychiatry Rating Scale (BPRS), Social Skills Psychometric Instruments (SSPI), and Ability of Daily Living Scale (ADL) between the two groups. Following the treatment, both groups exhibited reduced levels of TNF-α and IL-1β compared to pre-treatment levels, with the gene-guided group showing even lower levels (p<0.05). Conversely, the levels of NGF and BDNF increased in both groups post-treatment, with the gene-guided group demonstrating even higher levels (p<0.05). Additionally, the PANSS and BPRS scores decreased in both groups after treatment, with the gene-guided group showing even lower scores (p<0.05). On the other hand, both groups’ SSPI and ADL scores increased post-treatment, with the gene-guided group exhibiting higher scores (p<0.05). The overall efficacy of the treatment in the gene-guided group was superior to that in the conventionally treated group (p<0.05). Personalized medication guided by pharmacogenetics has the potential to enhance cognitive function, facilitate neurological recovery, improve social functioning, and enhance the daily living skills of individuals with schizophrenia, thereby facilitating their successful reintegration into society.